Adèle, version abâtardie de Jane Eyre - Claire Bazin (Revue LISA)
Adèle is a rewriting of the story of Jane Eyre published 150 years before. Emma Tennant, who is a specialist in the field of « revisions » puts Adèle, Jane’s young pupil in the Ur-text, in the limelight by giving her a « story  of her own », as if she were taking her revenge on the original text which had given her so insignificant a part.